2005
DOI: 10.1021/ma051954i
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Propagation Rate Coefficient of Nonionized Methacrylic Acid in Aqueous Solution from Low Monomer Concentrations to Bulk Polymerization

Abstract: The propagation rate coefficient, k p , for free-radical polymerization of nonionized methacrylic acid (MAA) in aqueous solution has been studied via pulsed laser polymerization (PLP) in conjunction with aqueous-phase size-exclusion chromatography (SEC). The PLP-SEC experiments were carried out between 20 and 80 °C within the entire concentration range from dilute solution containing 1 wt % MAA up to bulk MAA polymerization. The k p values which are determined under the assumption that the relevant monomer con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
266
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(293 citation statements)
references
References 25 publications
24
266
1
2
Order By: Relevance
“…The effect of the solids content on the conversion indicates that the dependence of the polymerization rate on the monomer conversion is not first order for any of the two monomers. This has been reported for the aqueous solution homopolymerization of MAA [19][20][21]25,42]. It has been found that the propagation rate coefficient of MAA was a function of the concentration of the monomer in the aqueous phase and of the ionization degree.…”
Section: Maa-co-pegma5 (5 Ethylene Glycol Units)mentioning
confidence: 53%
See 3 more Smart Citations
“…The effect of the solids content on the conversion indicates that the dependence of the polymerization rate on the monomer conversion is not first order for any of the two monomers. This has been reported for the aqueous solution homopolymerization of MAA [19][20][21]25,42]. It has been found that the propagation rate coefficient of MAA was a function of the concentration of the monomer in the aqueous phase and of the ionization degree.…”
Section: Maa-co-pegma5 (5 Ethylene Glycol Units)mentioning
confidence: 53%
“…In addition to the effect of the monomer concentration on the k p , the ionization degree also affects the kinetics of acidic water-soluble monomers like AA and MAA. For instance, for MAA, one of the monomers used in this work, Lacík et al [19][20][21]25] have determined the effect of the ionization degree (from non-ionized to fully ionized conditions) and found that the k p significantly reduces on going from non-ionized form to the fully ionized form, and that this decrease diminishes as MAA concentration increases.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, previous studies using PLP-SEC, the IUPAC recommended method for determining kp [13], have examined the radical polymerization behavior of other water-soluble monomers, including non-ionized to fully ionized acrylic and methacrylic acids [14][15][16][17] and acrylamide [18]. It is now known that the polymerization kinetics of these monomers in water differ significantly from those of the same monomers in organic solvents, with the kp values of non-ionized acrylic acid and methacrylic acid significantly higher in water than in methanol and dimethyl sulfoxide (DMSO) [19].…”
Section: Introductionmentioning
confidence: 99%